Policy processes underpinning universal health insurance in Vietnam - Bui T. T. Ha; Scott Frizen; Le M. Thi; Doan T. T. Duong; Duong M. Duc (Taylor & Francis Group, 2014)
Background: In almost 30 years since economic reforms or 'renovation' (Doimoi) were launched, Vietnam has achieved remarkably good health results, in many cases matching those in much higher income countries. This study explores the contribution made by Universal Health Insurance (UHI) policies, focusing on the past 15 years. We conducted a mixed method study to describe and assess the policy process relating to health insurance, from agenda setting through implementation and evaluation. Design: The qualitative research methods implemented in this study were 30 in-depth interviews, 4 focus group discussions, expert consultancy, and 420 secondary data review. The data were analyzed by NVivo 7.0. Results: Health insurance in Vietnam was introduced in 1992 and has been elaborated over a 20-year time frame. These processes relate to moving from a contingent to a gradually expanded target population, expanding the scope of the benefit package, and reducing the financial contribution from the insured. The target groups expanded to include 66.8% of the population by 2012. We characterized the policy process relating to UHI as incremental with a learning-by-doing approach, with an emphasis on increasing coverage rather than ensuring a basic service package and financial protection. There was limited involvement of civil society organizations and users in all policy processes. Intertwined political economy factors influenced the policy processes. Conclusions: Incremental policy processes, characterized by a learning-by-doing approach, is appropriate for countries attempting to introduce new health institutions, such as health insurance in Vietnam. Vietnam should continue to mobilize resources in sustainable and viable ways to support the target groups. The country should also adopt a multi-pronged approach to achieving universal access to health services, beyond health insurance.